558 Changing drug overdose deaths patterns where US rates are highest: global implications. (20th November 2022) - Smith, Gordon
Abstract : Background: West Virginia(WV) drug poisoning rates were low before 2000 but now are the nation's highest. We explore the role of excessive opioid prescribing in imitating this epidemic. Methods: WV age-adjusted overdose fatality trends 1979 to 2020 were examined along with toxicology data from our medical examiner(ME) containing drug levels on all drug-involved deaths in WV. Percapita opioid prescribing rates was available 1997–2017. Results: Fatal drug overdose rates increased from 3.3/100, 000 in 2000 to 83.6 in 2000. WV percapita morphine milligram equivalent (MME) opioid prescription rates increased from 137 in 1997 to 1, 171 in 2011 (850% increase) but decreased to 554 in 2017. Corresponding with 2012 decline in prescribed opioids, prescription drug involvement deaths declined steadily while 2011–2013 overall overdose rates flattened. However, in 2012 heroin deaths began rising. In 2014 introduction of fentanyl began an unprecedented increase in overall fatality rates peaking in 2017. In 2018–19 rates declined but began to rise again corresponding with COVID-19 pandemic. More detailed time series analyses of temporal correlations of opioid prescription and overdose rates, including multivariate trends will be presented. Discussion: Unlike urban drug problems, the WV epidemic origins are largely iatrogenic, starting with extremely high opioid prescription rates. As predicted by the Iron Law of Prohibition, sudden decreases in the availability of prescription opioids were associated with an increased use of illicit, more potent opioids. This presentation will outline the progression of the rural drug problem in WV including harm-reduction efforts. Learning Outcomes: Discuss global implications of findings and lessons learned.